Systems Analysis by Graph Theoretical Techniques: Assessment of the Agricultural Innovation System of Azerbaijan - Temel, Tugrul; Janssen, Willem G.; Karimov, Fuad (International Service for National Agricultural Research, 2001)
This study introduces a graph-theoretic method for assessing linkages between components of a system and applies it to characterize the agricultural innovation system of Azerbaijan. The method promises wide applications among policy makers who are interested in assessing alternative innovation policies and/or programs by identifying effective pathways of interactions between the components and the constraints that hinder these interactions. Empirical findings suggest that there is ample scope for intermediary organizations to facilitate effective flow of knowledge between the public and the private components. But the development of such organizations calls for an enabling institutional environment. A second characteristic is that the growth of new links and/or the strengthening of the existing ones are constrained mainly by limited financial and human resources. Last but not least, the national research system should adopt a more proactive approach to collaborative research with international organizations. But this approach requires national research organizations to adopt flexible management styles.